The Rapamycin derivative RAD inhibits mesangial cell migration through the CDK-inhibitor p27KIP1 - Daniel, Christoph; Pippin, Jeffrey; Shankland, Stuart; Hugo, Christian (Laboratory Investigation, 2004)
The link between mesangial cell (MC) proliferation and migration during glomerular repair in the experimental mesangial proliferative glomerulonephritis suggests that cell cycle regulation and cell migration require similar pathways, such as cell cycle proteins. The immunosuppressant RAD inhibits mesangial cell (MC) proliferation via G1/S arrest. Moreover, RAD dramatically impairs glomerular healing in the anti-Thy1 model. We tested the hypothesis that RAD alters MC migration in vitro and that this effect was mediated by the CDK-inhibitors p21CIP1 and p27KIP1. Using a modified Boyden chamber in vitro migration assay, our results showed that RAD dose dependently (1-50 nM) inhibited fibronectin-induced chemotaxis in wild-type (wt) MC. RAD treatment prevented the decrease in p27KIP1 induced by mitogenic growth factors, but had no effect on p21CIP1 by Western blot analysis. The antimigratory effect of RAD in wt MC was substantially dependent on p27KIP1, but not p21CIP1, since the inhibitory effects of 1-10 nM RAD on MC migration were similar in p21 CIP1 deficient and wild-type MC. The effect of RAD on MC migration was also examined in the anti-Thy1 model by BrdU-labeling of proliferating MC on day 3 that typically repopulate the glomerulus from the hilus. A control biopsy on day 3 was taken to define the starting point prior to the initiation of RAD (3 mg/kg or placebo). MC migration was determined on day 7 by measuring the distances of BrdU-labeled MC (OX-7+/BrdU+cells) from the glomerular hilus using computerized morphometry. RAD significantly reduced the migratory response of BrdU-labeled MC compared to controls. We conclude that the immunosuppressant RAD effectively inhibits MC migration in vivo and in vitro thereby limiting the normal glomerular repair process after severe injury. Moreover, RAD-induced inhibition of MC migration in vitro is partially mediated by the CDK-inhibitor p27KIP1, but not p21CIP1.
Created from Fastlane, Scopus look-up
Keywords: Anti-Thy1 model; CDK-inhibitors; Glomerular migration; Glomerular repopulation; RAD